PENINGKATAN KUALITAS LAYANAN GURU MELALUI PENGEMBANGAN KEPRIBADIAN GURU DAN KEADILAN ORGANISASI - Sri Setyaningsih; Kania Rubiati (Fakultas Keguruan dan Ilmu Pendidikan Universitas Pakuan, 2020)
IMPROVING THE QUALITY OF TEACHER SERVICES THROUGH THE DEVELOPMENT OF TEACHERS PERSONALITY AND ORGANIZATIONAL JUSTICEThe quality of teacher service is an important element related to achieving national education goals and developing Indonesian people as a whole. The initial survey of the service quality of Civil Servant teachers at Bogor Senior High Schools has not yet achieved maximum results. Therefore, the quality of teacher services is interesting to study. This study aims to find out how the quality of teacher services can be improved by examining the relationship between teacher service quality and teacher personality variables and organizational justice. This research uses correlational statistical methods and analyzes the system method. The unit of analysis for the study was the high school civil servant teachers with a population of 279 and a sample of 103 teachers. The results showed that there was a positive relationship between teacher personality and teacher service quality with the strength of the relationship ry1 = 0.421 and there was a positive relationship between organizational justice and teacher service quality with the strength of the relationship ry2 = 0.297 so that the quality of teacher services could be improved through teacher personality and organizational justice. The results of this correlation are then integrated with the SITOREM method in order to obtain a way to improve the quality of teacher services based on personality development and organizational justice through strengthening indicators. The results of SITOREM show that efforts to improve the quality of teacher services can be done by improving the following indicators in order of priority improvement: (1) stable emotions, (2) openness to experience (3) procedural justice (4) responsiveness (5) attention. The next effort is to maintain 9 indicators that are in good condition, namely: (1) sincerity (2) enthusiasm (3) agreement (4) interpersonal justice (5) informational justice (6) distributive justice (7) physical appearance (8) assurance (9) ) reliability.